EVOLUTION OF THE FOREIGN POLICY STRATEGY OF THE REPUBLIC OF TURKEY IN THE AFRICAN REGION (Вісник: Міжнародні відносини, 2024)
Considering the intensification of the activities of the Republic of Turkey in Africa, it is relevant to study the evolution of the country's foreign policy strategy in the region and the current state of Turkish-African relations. The article examines the main stages of formation and traces the dynamics of Turkey's foreign policy on the African continent. Special attention is paid to historical ties in the Ottoman period, as well as the period of significant development of bilateral and multilateral relations at the end of the 20th – beginning of the 21st century. Considering Turkey's activities in various directions, the main achievements in relations with African states in the political, trade-economic, military-security, cultural and other spheres were analyzed, and special attention was drawn to the key problems that prevent further growth of cooperation.
Keywords: Republic of Turkey, Africa, foreign policy strategy, humanitarian diplomacy, "soft power"